Oxidative stress induces cortical stiffening and cytoskeletal remodelling in pre-apoptotic cancer cells - Aiman Jalmukhambetova; Aidana Baltabekova; Aizhan Tolebay; Nargiz Rakhimgerey; Ferdinand Molnár; Tri Thanh Pham; Agata N. Burska; Dos D. Sarbassov (Cell Stress)
An imbalanced production of reactive oxygen species (ROS) is linked to various aspects of cancer development, including cytoskeletal remodelling. However, the relationship between ROS, actin and cellular stiffness remains controversial. Here, we show that oxidative stress increases cortical stiffness in pre-apoptotic colon and pancreatic cancer cells via localized F-actin polymerization in the apical cortex — independent of changes in total F-actin levels. Using atomic force microscopy and flow cytometry, we demonstrate this effect across multiple ROS inducers: the combination of arsenic trioxide and D-enantiomer of vitamin C, hydrogen peroxide, and rotenone. These findings explain previously debated relationships on how ROS influence actin organization, which may affect cellular stiffness. By separating total from cortical actin effects, our study reveals a redox-sensitive mechanism that governs cytoskeletal remodelling and may impair cancer cell migration.